Desenvolvimento de uma topologia híbrida a três fios para regulação de tensão aplicada em microcentrais hidrelétricas - Tischer, Celso Becker (2013)
This dissertation presents the study of a three-wire hibrid topology for voltage regulation for micro-hydroelectric generators that use self-excited induction in isolated operation. Initially, a literature review is presented in order to identify the main voltage regulation topologies applied to self-excited induction generators in the literature. From this review, a hybrid topology is proposed, which aims to regulate the voltage supplied by the generator to the isolated system. Thus, the mathematical modeling of the system is presented, comprising induction generator, the excitation capacitor, switched capacitor banks for voltage regulation, inductors filter and static reactive compensator. The following presents a control method based on reactive power control and design of switched capacitor banks using as reference the reactive power of the induction generator and static reactive compensator. The simulation and experimental results are presented to validate the proposed method. The use of the three-wire hybrid topology made of switched capacitor banks in conjunction with the static reactive compensator voltage regulation can be considered an addition to the scientific literature.